A philosophical approach to spiritual development in family management - Aung, Maulana Akbar Shah @ (2021)
Philosophy is a study of the fundamental of our existence, ideology, wisdom, Psyche, and values essential to understand the reality of every nature of humanity and the universe. It is known that the process of spiritual wellbeing can be identified through human mental power and wisdom. Thus, the philosophical approach to the understanding of spiritual development in family management is relatively appropriate. The spiritual wellbeing of a family is suggestively portrayed with humanistic and spiritual values such as mannerism, morality and conviction in religious belief. It is no doubt that a successful family is established by proper parental supervision followed by the appropriate participation of children. Thus, it is important to study every conduct and task of every family member, including parents. Moreover, there are signs of spiritual development that come along with every act of the family member. Therefore, the significance of notification in learning and teaching of those spiritual signs must be taken considerably. In addition, parents must continuously shadow the process of spiritual growth in their family because it will support its members derailing from the path of spiritual wellbeing. In this way, vivid growth of spiritual values, moralities, excellent ethics, and a good culture flourished in the family. This research is conducted through the qualitative research methodology, and it will be presented in the upcoming scholarship advancement symposium, 2021.